2002
DOI: 10.1002/cne.10434
|View full text |Cite
|
Sign up to set email alerts
|

Laminin chains in rat and human peripheral nerve: Distribution and regulation during development and after axonal injury

Abstract: During nerve growth, axons are dependent upon contact with matrix components, such as laminins, for elongation, guidance, and trophic support. Semiquantitative in situ hybridization histochemistry and immunohistochemistry (IHC) were used to identify laminin chains in normal peripheral nerves, during postnatal development, after sciatic nerve transection (SNT), and after sciatic nerve crush (SNC). Laminin alpha2, alpha4, beta1, beta2, and gamma1 chain mRNAs were all expressed at high levels in newborn rat sciat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
3
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 113 publications
3
58
3
1
Order By: Relevance
“…This is in contrast to what has been found in dy/dy mice, which lack laminin-2 and display a moderate myelination defect in some parts of the CNS (Chun et al, 2003). In peripheral nerves however, the laminin ␣4 chain is likely present in the basal lamina as the ␣ chain in laminin-8 (Wallquist et al, 2002). Given the fact that a large part of human cases of peripheral neuropathy remains etiologically unknown, and also that a defect in laminin ␣2 production is seen in the human disease MDCMD, it may well be that also laminin ␣4 has a human correlate involving a peripheral neuropathy.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…This is in contrast to what has been found in dy/dy mice, which lack laminin-2 and display a moderate myelination defect in some parts of the CNS (Chun et al, 2003). In peripheral nerves however, the laminin ␣4 chain is likely present in the basal lamina as the ␣ chain in laminin-8 (Wallquist et al, 2002). Given the fact that a large part of human cases of peripheral neuropathy remains etiologically unknown, and also that a defect in laminin ␣2 production is seen in the human disease MDCMD, it may well be that also laminin ␣4 has a human correlate involving a peripheral neuropathy.…”
Section: Discussioncontrasting
confidence: 81%
“…In a previous study we have shown that the endoneurial basal lamina of peripheral nerves not only contains laminin-2 (␣2␤1␥1) but also laminin-8 (␣4␤1␥1) (Wallquist et al, 2002). Considering the profound effects of laminin-2 deficiency and the importance of basal lamina proteins for cellular interactions, it is of obvious importance to elucidate the function of laminin-8 in the peripheral nerve.…”
Section: Introductionmentioning
confidence: 99%
“…Performance in the behavioral tests was most severely compromised in the DKO, with trembling on the beam, ataxia, and slipping of the hindlimbs, and this was apparently attributable to a more prominent delay in the axonal segregation and a more pronounced lack of C-fibers relative to the Lam␣4 Ϫ/Ϫ mice. Laminin ␣4 is mainly expressed in immature, developing nerves (Patton et al, 1997;Nakagawa et al, 2001;Wallquist et al, 2002), which may account for the partial recovery of the axonal segregation observed in the Lama4 Ϫ/Ϫ mice over 1 year of age. Nonsegregated axons are prominent in both young and old DKO mice, signifying a permanent defect attributable to the absence of the normally constitutively expressed collagen XV.…”
Section: Discussionmentioning
confidence: 99%
“…Many nerve ECM molecules such as WARP (5), laminins (22), and nidogens (23) are expressed highly during early development and myelination but are down-regulated at the transcriptional level in adult nerve tissues except in response to injury (22,23). A disorganization of collagen networks in nerve, therefore, may not necessarily undergo repair because it is not severe enough to compromise many normal functions.…”
Section: Discussionmentioning
confidence: 99%